2006
DOI: 10.1002/ijc.22098
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of doxorubicin resistance in breast cancer cells by photochemical internalization

Abstract: Multiple drug resistance (MDR) is a problem that seriously reduces the efficacy of many chemotherapy agents. One mechanism for MDR is increased acidification of endocytic vesicles and increased cytosol pH, so weak base chemotherapeutic agents, including doxorubicin, are trapped in endocytic vesicles and exhibit a drug resistant phenotype. Treatments that selectively reverse this accumulation may therefore reverse the MDR phenotype. Photochemical internalization (PCI) is a novel technology developed for site-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
78
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 34 publications
7
78
0
Order By: Relevance
“…However, if the membranes of these intracellular organelles are broken down by photochemical internalization (PCI), the macromolecules can become biologically active. This mechanism has been shown to overcome the resistance of some breast cancer cells to chemotherapy agents such as doxorubicin [40] and may be a way of undertaking gene transfer [41]. Preliminary clinical trials are already underway on the PCI of bleomycin using the photosensitizer TPCS2a (Amphinex, a chlorin derivative), on advanced head and neck cancers.…”
Section: (A) Photochemical Internalizationmentioning
confidence: 99%
“…However, if the membranes of these intracellular organelles are broken down by photochemical internalization (PCI), the macromolecules can become biologically active. This mechanism has been shown to overcome the resistance of some breast cancer cells to chemotherapy agents such as doxorubicin [40] and may be a way of undertaking gene transfer [41]. Preliminary clinical trials are already underway on the PCI of bleomycin using the photosensitizer TPCS2a (Amphinex, a chlorin derivative), on advanced head and neck cancers.…”
Section: (A) Photochemical Internalizationmentioning
confidence: 99%
“…PCI of gelonin and bleomycin and PCI-enhanced nonviral gene delivery has also been documented in vivo (Selbo et al, 2001;Berg et al, 2005;Dietze et al, 2005;Nishiyama et al, 2005;Ndoye et al, 2006). More recently, it was demonstrated that PCI could make the MDR breast cancer cell line MCF-7/ADR almost as sensitive to DOX as the fully sensitive cells, MCF-7, from the same origin by the intracellular release of endosome-lysosome-trapped DOX (Lou et al, 2006). Accumulation of DOX in MCF-7/ADR cells can be explained by the protonation, sequestration, and secretion (PSS) model (Altan et al, 1998), which suggests that weak base drugs are first protonated in acidified organelles of MDR cells, like lysosomes, where they are sequestered.…”
mentioning
confidence: 94%
“…Interestingly, doxorubicin did not show such cytotoxic activity against W iDr cell. As Lou et al (2006) stated, doxorubicin has selective activity against cancer cell line, especially to breast cancer cell line with the LC 50 value of 0.3 µg/ml.…”
Section: Cytoxicitymentioning
confidence: 92%